Stigmas and childhood traumas associated with psychological help-seeking in suicide attempted individuals - Ozsoy, Filiz; Tasci, Gulay; Kulu, Muberra; Okan, Fatih; Yilmaz, Seda; Korkmaz, Sevda; Atmaca, Murad (Wiley, 2022)
Purpose The aim was to investigate the possible associations of suicide attempt with childhood trauma, social support, psychological support seeking, stigmatizations. The study was case-control study and included 100 participants (50 suicide, 50 controls). Conclusion BDI, BAI scores were higher in the patient (p < 0.001). While scores of all-subscales of Childhood-Trauma-Questionnaire were higher (p < 0.05) in the patients, scores of Perceived-Social-Support were lower (p < 0.001). Repeating suicide attempts has higher Stigma-Scale-for-Receiving-Psychological-Help scores than the patients who attempted to the first time (p = 0.045). Practice Implication Suicide is relationship with more childhood traumas, less social support. Repeating suicide attempts, individuals felt public stigma for receiving psychological help.
Keywords: social support; stigma; suicide; trauma